2022
DOI: 10.3389/fendo.2022.982551
|View full text |Cite
|
Sign up to set email alerts
|

Female reproductive functions of the neuropeptide PACAP

Abstract: Pituitary adenylate cyclase activating polypeptide (PACAP) is a neuropeptide originally isolated as a hypothalamic peptide. It has a widespread distribution in the body and has a diverse spectrum of actions. Among other processes, PACAP has been shown to be involved in reproduction. In this review we summarize findings related to the entire spectrum of female reproduction. PACAP is a regulatory factor in gonadal hormone production, influences follicular development and plays a role in fertilization and embryon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 161 publications
1
3
0
Order By: Relevance
“…PACAP expression was positively correlated with the number of growing follicles and antral follicles (Figure 6A,B), and PAC1R was also positively correlated with the number of growing follicles (Figure 6C,D). Those results indicated that PACAP/PAC1R was commonly correlated with the follicle development, which is consistent with previous findings that PACAP/PAC1R is involved in regulating follicle development [27]. However, in this study, we found that PACAP/PAC1R is state-dependent for the follicle development.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…PACAP expression was positively correlated with the number of growing follicles and antral follicles (Figure 6A,B), and PAC1R was also positively correlated with the number of growing follicles (Figure 6C,D). Those results indicated that PACAP/PAC1R was commonly correlated with the follicle development, which is consistent with previous findings that PACAP/PAC1R is involved in regulating follicle development [27]. However, in this study, we found that PACAP/PAC1R is state-dependent for the follicle development.…”
Section: Discussionsupporting
confidence: 93%
“…In this pathway, PACAP uses the classical growth factor pathway to activate the expression of cFOS through MAPK phosphorylation of transcription factor ELK, and then activate FSH β [26]. Furthermore, PACAP and PAC1R may participate in the regulation of reproduction and follicle development via the HPO axis [27][28][29]. In studies, PACAP has been shown to inhibit FSH synthesis via the HPO axis to regulate reproduction [30].…”
Section: Introductionmentioning
confidence: 99%
“…Neuropeptides comprise a class of evolutionarily conserved 29,30 neuromodulators that control behavior-specific internal motive states associated with mating 31,32 , aggression [33][34][35] , social attachment 36 , feeding 37 and predator defense 38 , as well as other behaviors. Neuropeptides are well known to modulate synaptic strength and neural circuit properties such as patterns of oscillation [39][40][41] , but their role in implementing persistent activity and attractor dynamics has not been extensively studied in vertebrates.…”
Section: Introductionmentioning
confidence: 99%
“…The neuroendocrine system is responsible for regulating a number of functions in our body, including reproduction. Specifically, neuropeptides have been found to be involved throughout several phases of reproduction, from sexual behavior, conception, lactation, and parent-infant bonding, as their receptors are found throughout both the male and female reproductive tracts [7][8][9]. While most of the research investigated the role of numerous neuropeptides on female fertility and reproduction, there is evidence indicating their critical involvement in male fertility and sperm development [9][10][11].…”
Section: Introductionmentioning
confidence: 99%